Determining the probability of locating peaks using computerized peak-location methods in gamma-ray spectra as a function of the relative peak-area uncertainty. (January 2020) - Ali Santoro, M.C.; Anagnostakis, M.J.; Boshkova, T.; Camacho, A.; Iljadica, M.C. Fornaciari; Collins, S.M.; Perez, R. Diaz; Delgado, J.U.; Đurašavić, M.; Duch, M.A.; Elvira, V.H.; Gomes, R.S.; et al.
Abstract: The probabilities of locating peaks with a high relative peak-area uncertainty were determined empirically with nine types of peak-location software used in laboratories engaged in gamma-ray spectrometry measurements. It was found that it is not possible to locate peaks with a probability of 0.95, when they have a relative peak-area uncertainty in excess of 50%. Locating peaks at these relatively high peak-area uncertainties with a probability greater than 0.95 is only possible in the library-driven mode, where the peak positions are supposed a-priori. The deficiencies of the library-driven mode and the possibilities to improve the probabilities of locating peaks are briefly discussed. Highlights: The chance for finding peaks was determined for gamma-ray analyzing software. Peaks with urel < 50% for peak area are located with less than 0.8 probability. In the library-driven mode the chance to find peaks is unity at all uncertainties. At small peaks in the library-driven mode the uncertainties are larger.